Autophagy inhibitor enhance ZnPc/BSA nanoparticle induced photodynamic therapy by suppressing PD-L1 expression in osteosarcoma immunotherapy. (February 2019) - Yu, Wei; Wang, Yitian; Zhu, Jian; Jin, Libin; Liu, Bing; Xia, Kaishun; Wang, Junjie; Gao, Jianqing; Liang, Chengzhen; Tao, Huimin
Abstract: Elevated expression of programmed death ligand-1 (PD-L1) on the surface of tumor cells can exhaust cytotoxic T lymphocyte cells and lead to the failure of anti-tumor immunity during the course of tumor treatment. Here, we implemented a combined regimen of tumor resection and bovine serum albumin-Zinc phthalocyanine-induced photodynamic therapy (PDT). To overcome the long-distance metastasis of osteosarcoma, we also explored the effects of PD-L1 down-regulation with PDT and the autophagy inhibitor 3-MA on osteosarcoma treatment. A dramatic anti-tumor effect induced by PDT was observed in a partial resection model, which revealed the potential clinical application of PDT during tumor resection. Meanwhile, we also confirmed the down-regulation of PD-L1 in osteosarcoma in response to PDT and 3-MA treatment, which significantly inhibited tumor growth in a model of tumor metastasis. The immunological response induced by the combination of the autophagy inhibitor and PDT suppressed osteosarcoma in vitro and in vivo, which indicated the potential application of this regimen for preventing tumor metastasis. The combination of PDT with multiple therapies has a potentially bright future as an osteosarcoma treatment strategy.